Simultaneous Enantiodivergent Synthesis of Diverse Lactones and Lactams via Sequential One-Pot Enzymatic Kinetic Resolution–Ring-Closing Metathesis Reactions - Anna Brodzka; Dominik Koszelewski; Ryszard Ostaszewski (Molecules, 2022)
One of the goals of diversity-oriented synthesis is to achieve the structural diversity of obtained compounds. As most biologically active compounds are chiral, it is important to develop enantioselective methods of their synthesis. The application of kinetic resolution in DOS is problematic because of low efficiency (max. 50% yield) and many purification steps. The further derivatization of kinetic resolution products in DOS leads to the formation of a narrow library of compounds of the same stereochemistry. To overcome these limitations, we present a new concept in which the kinetic resolution is combined, the subsequent reaction of which in a one-pot protocol leads to the simultaneous formation of two skeletally and enantiomerically diverse platform molecules for DOS. Their further derivatization can gain access to a double-sized library of products in respect to a classical approach. The validity of our concept was evidenced in enzymatic kinetic resolution followed by a ring-closing metathesis cascade. From racemic carboxylic acid ester, a simultaneous formation of enantiopure lactones and lactams was achieved. These compounds are important building blocks in organic and medicinal chemistry and until now were synthesized in separate procedures.